Teacher Candidates’ Attitudes Towards the Teaching Profession in Turkey - Tok, Türkay Nuri (Alberta Journal of Educational Research, 2012)
This study examined the attitudes of teacher candidates in Turkey towards the teaching profession. Descriptive surveys were used and the research data was obtained from Pamukkale University Classroom Teaching students. During data analysis, the arithmetic means and standard deviations of the groups were calculated and a t-test and One-Way ANOVA were used. The attitudes of teacher candidates towards the teaching profession don’t vary in terms of “gender”, “type of teaching”, “type of high schools they graduate from” and in order of their preferences to be a teacher. More than half of the candidates choose the Classroom Teaching Program willingly and about all of them want to perform this profession, but their attitudes towards the teaching profession were not well developed. The majority of the participants were not satisfied with the University and faculty administrations and reopted that they don’t show enough effort required to develop themselves for the profession. It is found that the attitudes of students expressing their discontent are at a lower level. It is necessary to provide the teacher candidates not only with knowledge and skills, but also to help them develop the beliefs and positive attitudes related to the profession. Cette étude a porté sur les attitudes qu’ont des étudiants au programme de formation à l’enseignement en Turquie envers la profession enseignante. Nous avons effectué des sondages descriptifs auprès d’étudiants au programme de formation à l’enseignement d’enseignement en classe de la Pamukkale University. Pendant l’analyse des données, on a calculé les moyennes arithmétiques et les écarts types des groupes en appliquant un test t et une ANOVA unidirectionnelle. Les attitudes qu’ont les étudiants au programme de formation à l’enseignement envers la profession enseignante ne varient pas en fonction des critères suivants : « genre », « type d’enseignement », « type d’école secondaire fréquentée » et « désir de devenir enseignant ». Plus de la moitié des candidats choisissent de leur plein gré l’enseignement en classe et à peu près tous veulent poursuivre cette profession; pourtant leurs attitudes envers la profession enseignante n’étaient pas bien développées. La majorité des participants n’étaient pas satisfaits de l’université, ni de l’administration et ils ont signalé qu’ils ne démontraient pas suffisamment d’efforts nécessaires pour se développer comme enseignants. On a trouvé que les attitudes des étudiants qui exprimaient leur mécontentement étaient plus négatives. Il est nécessaire de non seulement transmettre aux étudiants au programme de formation à l’enseignement des connaissances et des compétences, mais aussi de les aider à développer des croyances et des attitudes positives par rapport à leur profession.